1982
DOI: 10.1002/1097-0142(19820801)50:3<478::aid-cncr2820500316>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination hyperthermia and radiation therapy for malignant melanoma

Abstract: Since 1975, clinical studies have been carried out to determine whether radiation when combined with localized hyperthermia evokes improved tumor control compared to that achieved with radiation alone. Local tumor hyperthermia was achieved using radiofrequency inductive heating at 27.12 MHz. In bulky lesions (<100 cm3), radiofrequency conductive heating at 13.56 MHz was also used. More than 100 lesions in 38 patients were treated with radiation alone and hyperthermia in combination with radiation. Most lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

1984
1984
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(29 citation statements)
references
References 15 publications
0
27
0
2
Order By: Relevance
“…Clinical investigations during the last decade have suggested that hyperthermia in combination with radiation therapy may be a promising modality for the treatment of cancer (Kim et al 1982, Perez er al. 1983, Luk et al 1984, Oleson er al.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical investigations during the last decade have suggested that hyperthermia in combination with radiation therapy may be a promising modality for the treatment of cancer (Kim et al 1982, Perez er al. 1983, Luk et al 1984, Oleson er al.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia involves two biological interactions with radiation, a radiosensitizing effect [9,10] and a direct cytotoxic effect on tumor cells [11] . When the target lesion is heated up to around 42 , the cancer-killing effect of radiation or anticancer drug is enhanced [12] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…It has also been noted that hyperthermia and radiation are synergistic. 21 Transcleral diathermy for small melanomas is effective22 but causes extensive damage to overlying sclera, with the risk of extrascleral spread. More recently, Finger et aP3 showed good tumour response histologically without significant damage to the sclera using a 5 to 8 GHz ophthalmic microwave applicator.…”
Section: Hyperthermic Treatmentmentioning
confidence: 99%